Gambaran Konsumsi Sayur dan Buah dengan Status Gizi Remaja di SMP Negeri 3 Abiansemal, Kabupaten Badung - Ni Komang Desi Dina Purwita; I Ketut Kencana; A.A. Ngurah Kusumajaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
The prevalence of low consumption of vegetable and fruit in population age 10 years is 93.6%, and the number in the province of Bali is 96.5%. The same prevalence in Badung Regency as much as 95.9%. This research aims to discuss the consumption of vegetable and fruit and nutritional status. This is a cross sectional study using 82 samples. The study found that 95.1% samples had less of vegetable consumption, and 56.1% had enough consumption of fruit. Most of sample about 71.9% had normal nutrition status, and 3.7% were thin category. However there were 14.6% samples fat and 9.8% were in obesity. Vegetable and fruit consumption should be increased in teenagers to prevent the occurrence of cancer.Keywords: vegetable and fruit, consumption, nutritional status